Phytochemical Composition and Antioxidant Properties of Avocado (Persea americana) Seed Extract from Aceh, Indonesia: Implications for Antihyperlipidemic Use in Postmenopausal Women - Nurbaiti, Nurbaiti; Fitri, Yulia; Fitriani, Fitriani; Humaira, Wardati; Triwibowo, Cecep (Malacca Pharmaceutics, 2025)
Avocado (Persea americana) is widely recognized for its high antioxidant capacity. Its rich phytochemical composition is crucial in mitigating oxidative stress and managing chronic conditions such as cardiovascular disease and hyperlipidemia. This study aimed to investigate the phytochemical profile, antioxidant activity, and antihyperlipidemic potential of ethanol extracts derived from avocado seeds. Phytochemical screening and Gas Chromatography-Mass Spectrometry (GC-MS) analysis were conducted to identify key chemical constituents, while antioxidant activity was assessed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. In addition, in-silico techniques were employed to evaluate the antihyperlipidemic potential of the bioactive compounds. Phytochemical analysis revealed a variety of bioactive compounds, including volatile compounds, steroids, and fatty acids, contributing to the extract's biological activity. The extract demonstrated strong antioxidant capacity, with an IC50 value of 20.83 ppm, indicating potent free radical scavenging ability. GC-MS analysis identified significant compounds such as Undec-10-ynoic acid, tetradecyl ester, and 9,12,15-Octadecatrienoic acid, 2-(acetyloxy)-1-[(acetyloxy)methyl] ethyl ester, which were further analyzed through molecular docking studies. These studies indicated their potential as inhibitors of hyperlipidemia-associated proteins, with binding energy values exceeding -6 kcal/mol. Moreover, ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) analysis demonstrated favorable pharmacokinetic profiles, including good absorption and low toxicity, positioning these compounds as promising candidates for therapeutic development. The findings of this study underscore the potential of avocado seed extract as a natural source of antioxidants and antihyperlipidemic agents. The identified bioactive compounds offer a promising therapeutic strategy for managing oxidative stress and lipid disorders, particularly in populations at heightened risk, such as postmenopausal women.